Electro-Acupuncture Affects the Activity of the Hypothalamic-Pituitary-Ovary Axis in Female Rats - Zhu, Hongmei; Nan, Sha; Suo, Chuanguang; Zhang, Qiulin; Hu, Manli; Chen, Rong; Wan, Juan; Li, Meng; Chen, Jianguo; Ding, Mingxing (Frontiers in Physiology, 2019)
Hypothalamic-pituitary-ovary (HPO) axis is a dominant system controlling ovulation during puberty. Electro-acupuncture (EA) has been widely used to cure the reproductive diseases associated with endocrinological disorders. However, whether EA treatment affect HPO axis activity of physiological animals and induce alterations on the hormones in the HPO axis were also unclear. Here, we performed the EA stimuli on bilateral acupoints of Sanyinjiao (SP6) and Zusanli (ST36) on female virgin rats every 3 days and for a total of 5 times. The results showed that, GnRH levels in hypothalamus were greatly upregulated in EA-treated rats than untreated animals at day 7 and 13. The serum levels for FSH and LH were severely reduced after EA treatment compared with EA-untreated animals at day 1, while were greatly increased at day 7 and 13. The serum concentrations of 17β-estradiol were lower in EA-treated rats versus untreated-animals at day 7, while were higher in EA-treated rats than other groups at day 13. However, the progesterone concentrations were lower in EA-treated rats than Control and Sham-EA rats both at day 7 and 13. More importantly, we found that the prostaglandin E2 level in serum was reduced in EA-treated rats versus untreated rats at day 1, while were upregulated at day 7 and 13. Conversely, the norepinephrine level in serum was increased at day 1, while were decreased greatly in EA-treated rats versus untreated rats at day 7 and 13. The current results demonstrated that EA could modulate homeostasis of HPO axis in physiologic rats which would be useful to clarify the mechanisms of EA application on pathological and physiological animals or human.